Analysis of exploitation control in typical groundwater over-exploited area in North China Plain. Issue 5 (4th April 2021) - Wang, Kairan; Chen, Huawei; Fu, Shidong; Li, Fulin; Wu, Zhen; Xu, Dandan
ABSTRACT: Groundwater is exploited extensively, continuously and in a disorderly way in the North China Plain (NCP), which leads to severe problems of groundwater over-exploitation, making it the largest groundwater funnel zone in the world. Based on a comprehensive treatment of over-exploited groundwater in Shandong province, this paper analyses and forecasts the water demand, supply and savings in over-exploited areas, and puts forward a method to analyse the potential for groundwater exploitation control, which provides technical support for the comprehensive analysis of exploitation control in over-exploited areas. As a result, under a 50% guaranteed rate of water supply, the potential for groundwater exploitation control in Shandong province over-exploited areas in 2020 and 2030 is 408 × 10 6 and 638 × 10 6 m 3, respectively. This study can serve as a useful reference for the comprehensive management of groundwater over-exploitation in NCP and other over-exploited areas around the world.